1961
DOI: 10.1111/j.1365-2672.1961.tb00247.x
|View full text |Cite
|
Sign up to set email alerts
|

The Microflora of the Rumen of the Young Calf: Ii. Source, Nature and Development

Abstract: SUMMARY Twelve calves of different sex and breed divided into four groups were used in the experiments. Each group received different rearing and diet treatment. Three hundred and nine samples of rumen contents were obtained by means of a stomach tube during the period from birth to three months of age. Streptococci, lactobacilli and coli‐aerogenes organisms were isolated and studied, and isolates were also made from various elements of the calves’ environment. Rapid development of the rumen flora occurred imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…(1958), and of Ziolecki and Briggs (1961) (2,16). While, viable counts of streptococci and lactobacilli, enumerated by using BL agar medium, were extremely higher than those enumerated by using TATAC and a modified LBS agar media (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1958), and of Ziolecki and Briggs (1961) (2,16). While, viable counts of streptococci and lactobacilli, enumerated by using BL agar medium, were extremely higher than those enumerated by using TATAC and a modified LBS agar media (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the development of rumen microbial populations in young calves have been carried out by a few workers (2,5,16). However, since information obtained on these studies so far is limited, it is necessary to clarify the role and importance of various kinds of microorganisms in the development of the rumen function.…”
mentioning
confidence: 99%
“…The high proportion of easily fermentable carbohydrates in the rumen starter (331 g kg -1 starch on a dry matter basis) surely allowed the proliferation of a wide variety of rumen bacteria [5]. Furthermore, it has been reported that the income of small amounts of milk into the rumen can allow the growth of some facultative anaerobic bacteria such as Lactobacillus spp., which have been described as one of the main bacterial species in the rumen of suckling calves [11,40]. The low pH values recorded at 21 and 30 days of age are compatible with the proliferation of this type of bacteria [11].…”
Section: Functional Groups Of Rumen Microorganisms According To Age Amentioning
confidence: 62%
“…Concentrate feeds promote a lower rumen pH (5.5) than forage (6.8) (Ziolecki and Briggs, 1961). Cellulolytic bacteria, such as Butyrivibrio fibrisolvens, Bacteroides succinogenes, Ruminococcus albus, and Ruminococcus flavefaciens, are extremely sensitive to changes in pH.…”
Section: Microbial Populationsmentioning
confidence: 99%
“…The rumen environment is rapidly colonized by microflora after birth (Ziolecki and Briggs, 1961). Populations of aerobic bacteria are first to colonize.…”
Section: Microbial Populationsmentioning
confidence: 99%